The Effect Of Human Resource Development On Employee Performance At The Binjai City Regional Inspectorate Office - Septy Wanna Masayu; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of Human Resource Development on Employee Performance at the Binjai City Regional Inspectorate Office. This type of research is quantitative causal associative, which aims to find out the relationship and influence between the two variables. The population in this study is 68 employees at the Binjai City Regional Inspectorate Office, with a sampling technique using saturated sampling. Data was obtained through the distribution of questionnaires to all respondents. The results of the study show that Human Resource Development has a positive and significant influence on Employee Performance, as evidenced by the results of the t-count test of 18,223 > t-table 1.66827, as well as a significance value of 0.000 < 0.05. A regression coefficient of 2,681 indicates that every 1 point increase in Human Resource Development will lead to an increase in Employee Performance by 2,681 points, assuming other variables remain constant. The results of the determination coefficient test showed an Adjusted R Square value of 0.832 or 83.2%, which showed that Human Resource Development had a very large influence on Employee Performance, with 16.8% influenced by other factors that had not been studied. Overall, the results of this study show that improving Human Resource Development can significantly improve Employee Performance at the Binjai City Regional Inspectorate Office.